Can History of Parasitic Diseases Increase Social Conservatism? Testing Behavioural Immune System Theory - Jędryczka, Wiktoria (Journal of Education Culture and Society, 2022)
Aim. Using available data from previously published study the hypothesis that individuals with broader disease history are more conservative than those, who were infected less often in the past was tested. Methods. Publicly available database containing data regarding perceived vulnerability to disease, social conservatism and participant’s history of parasitic disease was accessed. In the study 9409 cases from 43 countries were analysed. Results. When controlling for participant’s age, sex, education level, wealth and perceived infectability, it was found, that broader disease history was a significant predictor of social conservatism. Conclusions. Individuals, who were in the past infected with parasitic diseases more often, were observed to be more conservative than people, who had suffered from these diseases less often.